2006
DOI: 10.1128/aac.50.4.1372-1375.2006
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Target Site Penetration of Vancomycin in Diabetic Patients following Cardiac Surgery

Abstract: Soft tissue infections constitute a serious complication following surgery in diabetic patients and frequently require the administration of vancomycin. However, despite antibiotic treatment, mortality of patients with postoperative infections remains high and might be related to an impaired penetration of anti-infective agents to target tissues. Therefore, the present study was designed to measure vancomycin tissue concentrations in six diabetic and six nondiabetic patients after cardiac surgery. Vancomycin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 34 publications
1
73
0
3
Order By: Relevance
“…For instance, concentrations in epithelial lining fluid [61] and in soft tissue of diabetic patients are low [62]. Taking into account the good diffusion of linezolid to poorly vascularised tissues, this difference could explain the superiority of linezolid over vancomycin in SSTIs in patients with vascular insufficiency described in a subanalysis of a previous randomised study [63].…”
Section: Heteroresistancementioning
confidence: 98%
“…For instance, concentrations in epithelial lining fluid [61] and in soft tissue of diabetic patients are low [62]. Taking into account the good diffusion of linezolid to poorly vascularised tissues, this difference could explain the superiority of linezolid over vancomycin in SSTIs in patients with vascular insufficiency described in a subanalysis of a previous randomised study [63].…”
Section: Heteroresistancementioning
confidence: 98%
“…However, some studies have demonstrated that infection changes the physiological characteristics of the infected tissue due to the inflammatory process developed by host aiming to eliminate the invasive organism, as observed in soft tissue infections, septic shock, pneumonia or vascular alterations associated to diabetes. [9][10][11][12] In this context, it is not always possible to predict the antimicrobial-free fraction at the site of infection, based on the microdialysis data obtained in healthy tissue or unbound plasma levels.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, increased scrutiny of vancomycin tissue penetration and dosing methods has fostered debate over its role as the cornerstone for serious cSSTIs infections caused by resistant gram-positive organisms (Lipsky et al 2004;Stevens et al 2005;Skhirtladze et al 2006;Mohr and Murray 2007;Deresinski 2007). Vancomycin has long been the workhorse antimicrobial therapy for resistant gram-positive infections; however, increasing resistance in cSSTI pathogens and increasing reports of clinical failures have necessitated the search for alternative agents.…”
Section: Bennett Et Almentioning
confidence: 99%